Tibetan CSL learners' L2 Motivational Self System and L2 achievement. (April 2021) - Li, Ming; Zhang, Lubei
Abstract: Motivation, a key factor explaining learners' success or failure in learning a language, is a well-researched topic in the area of second language acquisition. The present paper reports on a study that draws on Dörnyei's (2009) Second Language Motivational Self System (L2MSS) to explore Tibetan students' motivation for learning Chinese as their second language (CSL) and its effect on their Chinese learning achievement (CA). 198 Tibetan students took part in a questionnaire survey and a follow-up Chinese language proficiency test. The results show that all three major components of the L2MSS, namely, the ideal L2 self (IS), the ought-to L2 self (OS), and the L2 learning experience (LE), can predict Tibetan students' intended learning effort (ILE) directly or indirectly. Learners' IS and OS have been found to be the positive direct predicator and the negative direct predicator of the CA respectively. The findings confirm the powerful strength of the tripartite L2MSS in predicting learners' ILE, explaining 55% of their variance, but a weak predicting power for the CA, explaining only 13% of its variance, in the Tibetan CSL context in mainland China. The results have significant pedagogical implications for CSL education in China and abroad.